Expectations, Plans, and Realizations in Theory and Practice - Nerlove, Marc (Econometrica, 1983)
[In this paper, I attempt to peek into the "black box" of the firm and explore some very simple models of expectation formation and planning using data on a group of French and German manufacturing firms who report over time on both expectations and their subsequent realizations. Important differences are obtained between the results for French firms and for German firms. For both groups, however, firms' expectations or plans are found to be much more concentrated in the no change category than are the realizations they forecast. Consistent biases in the other categories are found for the German, but not the French firms; for the former the conditional distributions of realizations, given prior expectations or plans, are stable over time, while they are unstable for the latter. Of the simple models dealing with the formation of price and demand expectations, the error-learning model (a form of adaptive expectations) gives the best and most parsimonious explanation of the data. Estimation of a joint error-learning model for price anticipations and production plans suggests that the two processes are nearly independent of one another for both groups. A conditional probability model relating production plans to expectations of future demand, inventory level, or order backlog appraisals and recent changes in demand, explains the data about as well as a mechanical error-learning model, but offers scope for improvement and more economic content. Deviations between prior expectations of demand and realizations in the current period are found to affect the deviations between price expectations and production plans from their respective realizations, except for French firms' price expectations. These and related variables and relationships are further explored in a recursive conditional log-linear probability model which is discussed in a sequel to the paper.]